Numerical modelling of the growth of polygonal fault systems - King, JJ; Roberts, DT; Cartwright, JA; Levell, BK (Elsevier, 2022)
Despite over three-decades of active research and wide debate in the published literature, the mechanisms that govern the growth of polygonal faults are poorly understood. Here we investigate the growth of polygonal faults using a suite of geomechanical finite element forward models that couple dynamic fault propagation, sedimentation, and the mechanical compaction of unconsolidated granular sediment. We undertook a suite of numerical model simulations to explore the relationships between varying fault plane dip, residual friction of the fault, and the bulk material properties of the sedimentary sequence hosting the polygonal fault system. We find that the growth of polygonal faults within laterally-pinned sedimentary tiers can be explained by gravity-driven differential compaction and does not require additional causative elements to explain the gross pattern of strain accumulation. We also find that the magnitude of fault throw is influenced by the material properties and the original fault plane dip, but is most sensitive to the residual friction angle. Our models yield values for maximum throw versus height for the faults that fall within the range of global values compiled for polygonal faults, and throw rates are comparable to those recently measured in naturally occurring polygonal faults.